THE LINK BETWEEN MIGRATION, REMITTANCES AND ECONOMIC GROWTH: EMPIRICAL EVIDENCE FROM ROMANIA - PIRVU, Ramona; BADARCEA, Roxana; MANTA, Alina; FLOREA, Nicoleta (Theoretical and Practical Research in Economic Fields, 2018)
The paper investigates the causal link between remittances and economic growth in Romania. Starting from the debates regarding the relative contribution of international migrants’ remittances to sustainable economic development, this paper proposes an econometric analysis of the effects of remittances on the Romanian economy. The article shows that remittances have a positive effect on the current account of external balance of payments and they can replace external financial assistance flows, including foreign loans. Significant inflows of remittances can offset the current account deficit of the balance of payments, reducing the likelihood balance of payments crisis. At the same time remittances will increase aggregate demand, which has the effect of increasing inflation, currency appreciation and widening trade deficit. We showed also that remittances can exert positive influences on the process of investment, especially through the creation of numerous small enterprises.